2021
DOI: 10.1002/art.41894
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ciliary Protein Intraflagellar Transport Protein 88 in the Regulation of Cartilage Thickness and Osteoarthritis Development in Mice

Abstract: Objective. Mechanical and biologic cues drive cellular signaling in cartilage development, health, and disease. Primary cilia proteins, which are implicated in the transduction of biologic and physiochemical signals, control cartilage formation during skeletal development. This study was undertaken to assess the influence of the ciliary protein intraflagellar transport protein 88 (IFT88) on postnatal cartilage from mice with conditional knockout of the Ift88 gene (Ift88-KO).Methods. Ift88 fl/fl and aggrecanCre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Taken together, our data establish the cilium as a cellular location for ENPP- Article in cilia, mammalian ENPP1 loss of function manifests signs of ciliopathies, such as accelerated ossification, hearing impairment, and altered insulin metabolism and immune response. 39,40 To validate the IL2-enriched category of EV cargo candidates (Category I; Figure 2F), we focused on another nucleic acid binding protein, minichromosome maintenance complex component 3 (MCM-3) licensing factor, and generated transgenic animals expressing MCM-3::mScarlet, driven by its native promoter. MCM-3::mScarlet showed nuclear localization in the developing embryo, consistent with the known function of the MCM proteins in DNA replication licensing and DNA helicase activity of the MCM-2-7 complex 41 (Figure S5A).…”
Section: Integration With Cell-specific Transcriptomic Datasetsmentioning
confidence: 99%
“…Taken together, our data establish the cilium as a cellular location for ENPP- Article in cilia, mammalian ENPP1 loss of function manifests signs of ciliopathies, such as accelerated ossification, hearing impairment, and altered insulin metabolism and immune response. 39,40 To validate the IL2-enriched category of EV cargo candidates (Category I; Figure 2F), we focused on another nucleic acid binding protein, minichromosome maintenance complex component 3 (MCM-3) licensing factor, and generated transgenic animals expressing MCM-3::mScarlet, driven by its native promoter. MCM-3::mScarlet showed nuclear localization in the developing embryo, consistent with the known function of the MCM proteins in DNA replication licensing and DNA helicase activity of the MCM-2-7 complex 41 (Figure S5A).…”
Section: Integration With Cell-specific Transcriptomic Datasetsmentioning
confidence: 99%
“…Deletion of IFT88 in cartilage causes several OA phenotypes with increased expression levels of degeneration markers, including MMP13, collagen type X, Adamts5, and Runx2 [ 8 ]. Similarly, the Bardet-Biedl syndrome 1 (Bbs1), Bbs2, or Bbs6 gene mutation mouse model developed OA-like cartilage abnormalities including proteoglycan loss, small surface fibrillation, marked atrophy of the cartilage, and increased MMP13 expression [ 42 , 43 ]. Moreover, IFT88 deletion following surgical destabilization of the medial meniscus was found to have increased OARSI scores of cartilage damage mouse [ 43 ].…”
Section: Primary Cilia and Ciliary Proteins In Skeletal Diseasesmentioning
confidence: 99%
“…Similarly, the Bardet-Biedl syndrome 1 (Bbs1), Bbs2, or Bbs6 gene mutation mouse model developed OA-like cartilage abnormalities including proteoglycan loss, small surface fibrillation, marked atrophy of the cartilage, and increased MMP13 expression [ 42 , 43 ]. Moreover, IFT88 deletion following surgical destabilization of the medial meniscus was found to have increased OARSI scores of cartilage damage mouse [ 43 ]. All these studies suggested that primary cilia are essential for cartilage development and prevent its degeneration.…”
Section: Primary Cilia and Ciliary Proteins In Skeletal Diseasesmentioning
confidence: 99%
“…Pharmaceutically, the long-term application of dexamethasone increases the calcium content of CCL in both murine model and OA patients, which can also predispose OA and accelerate OA progression ( Chen et al, 2021 ). In the contrast, a list of molecules that perform chondroprotective roles through inhibition of cartilage calcification is also found, including ciliary protein intraflagellar transport protein 88 (IFT88) ( Coveney et al, 2022 ), betaine ( Yajun et al, 2021 ), gasotransmitter hydrogen sulfide (H 2 S) ( Nasi et al, 2021 ), and Tougu Xiaotong capsule ( Li et al, 2013 ). Phosphocitrate (PC) and its analogs can restrain endochondral ossification by suppressing the hypertrophic phenotype ( Hartlev et al, 2018 ).…”
Section: Alteration and Oa Progressionmentioning
confidence: 99%